Parent-initiated posthumous-assisted reproduction revisited in light of the interest in genetic origins - Bokek-Cohen, Ya'arit (Journal of medical ethics, 2023)
A rich literature in bioethics argues against the use of anonymous gamete donation in the name of the ‘interest in knowing one’s genetic origins’. This interest stems from medical as well as psychosocial and identity reasons. The term ‘genealogical bewilderment’ has been coined to express the predicament of those deprived of access to information about their origins. Another rich body of literature in bioethics discusses arguments for and against posthumous-assisted reproduction (PAR), with a recent focus on PAR that is initiated by the parents of a deceased man (rather than his partner). This paper revisits arguments against PAR, in light of arguments regarding the interest in knowing one’s genetic origins. Limiting the discussion to the specific context of parent-initiated PAR (PIPAR), we argue that the use of cryopreserved sperm from a deceased identifiable man in the context of PIPAR may be ethically preferable when compared with the use of anonymous donor sperm, since it allows genealogical certainty, that is, giving the prospective child access to information about the identity, life story and ancestry of the genetic progenitor as well as genealogical embeddedness, that is, close relationship with extended family members.